Electrolyte Effects on the Electrochemical Reduction of CO2 - Moura de Salles Pupo, Marilia; Kortlever, Ruud (Chemphyschem, 2019)
The electrochemical reduction of CO2 to fuels or commodity chemicals is a reaction of high interest for closing the anthropogenic carbon cycle. The role of the electrolyte is of particular interest, as the interplay between the electrocatalytic surface and the electrolyte plays an important role in determining the outcome of the CO2 reduction reaction. Therefore, insights on electrolyte effects on the electrochemical reduction of CO2 are pivotal in designing electrochemical devices that are able to efficiently and selectively convert CO2 into valuable products. Here, we provide an overview of recently obtained insights on electrolyte effects and we discuss how these insights can be used as design parameters for the construction of new electrocatalytic systems. The electrochemical reduction of CO2 to fuels and chemicals can potentially close the carbon cycle. Here, the authors discuss the importance of the electrolyte in determining the outcome of the reaction. They highlight recently obtained insights on electrolyte effects and discuss how the electrolyte choice can be used as a design parameter for more efficient electrocatalytic systems.